Impact of advanced maternal age on adverse infant outcomes: A Japanese population-based study. (November 2019) - Koshida, Shigeki; Arima, Hisatomi; Fujii, Takako; Ito, Yoshiya; Murakami, Takashi; Takahashi, Kentaro
Abstract: Objective: The number of births among women of higher age has been rapidly increasing in many countries for several decades. While recent epidemiological studies on the impact of maternal age on infant outcomes in developed countries have evaluated the outcomes of singleton infants, few population-based studies have investigated all deliveries including multiple births. Thus, we aimed to assess the impact of maternal age on adverse infant outcomes using data from all birth certificates, including multiple births, in Shiga prefecture, Japan. Study design: The data from all birth certificates in Shiga Prefecture from 2013 to 2014 (23, 294 births from 23, 048 mothers) were obtained. We evaluated the impact of maternal age on adverse infant outcomes, including small for gestational age (SGA), low birth weight (LBW), and preterm birth (PTB). A multivariable logistic regression analysis was performed to determine adjusted odds ratios (aORs) for infant outcomes with various maternal factors, including multiple pregnancies. Statistical analysis for trend was performed using the Jonckheere-Terpstra test. Results: The incidence rates of adverse infant outcomes began to increase at a maternal age of 30 years. A maternal age of ≥35 years was associated with significantly increased risks of adverse infant outcomes, including SGA (adjusted odds ratio [aOR]: 1.15, 95% confidence interval [95% CI]: 1.03–1.29), LBW (aOR: 1.29, 95% CI: 1.16–1.43), and PTB (aOR: 1.17, 95%CI: 1.04–1.33). Conclusions: The risk of adverse infant outcomes was significantly increased in women older than 35 years of age. These data would be useful for younger women to decide family-planning in advance.